Barriers faced by Grameenphone limited due to regulation and the expectations of the young users in Dhaka city regarding the value added services - Reza, Afia Farzin (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.